2012
DOI: 10.1189/jlb.0811410
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors in the host defense against Pseudomonas aeruginosa respiratory infection and cystic fibrosis

Abstract: TLRs function in innate immunity by detecting conserved structures present in bacteria, viruses, and fungi. Although TLRs do not necessarily distinguish pathogenic organisms from commensals, in the context of compromised innate immunity and combined with pathogens' effector molecules, TLRs drive the host response to the organism. This review will discuss the evidence and role(s) of TLRs in the response to the opportunistic bacterial pathogen, Pseudomonas aeruginosa, as it relates to respiratory infection and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 110 publications
0
54
1
2
Order By: Relevance
“…Zymosan is a common PAMPs expressed by yeast, and functions as a ligand of TLR2 [39]. TLR2 can also be activated by lipoproteins or lipopeptides located on the outer membrane of PA [40] and other pathogens [41]. It is reported that activation of TLR2 enhanced autophagy of L. monocytogenes [41].…”
Section: Discussionmentioning
confidence: 98%
“…Zymosan is a common PAMPs expressed by yeast, and functions as a ligand of TLR2 [39]. TLR2 can also be activated by lipoproteins or lipopeptides located on the outer membrane of PA [40] and other pathogens [41]. It is reported that activation of TLR2 enhanced autophagy of L. monocytogenes [41].…”
Section: Discussionmentioning
confidence: 98%
“…Initiation of a protective immune defence against a particular pathogen requires that the pathogen be processed efficiently by the immune system [24]. Although the conventional inactive H9N2 vaccines play a protective role to against H9N2 in certain extent, but their protective effect in eliminating clinical signs of illness do not compare with H9N2 vaccine.…”
Section: Biology Progress Category Analysis and Validationmentioning
confidence: 98%
“…Alterations in fatty acid saturation is a key property that controls stiffness and elasticity of PMs, and is a well-known mechanism for adaptation to distinct temperatures. It has been previously shown that polyunsaturated fatty acids (PUFAs) can impair lipopolysaccharide (LPS)-mediated activation of TLR4 which eventually promotes the activation of the nuclear factor kappa B (NFkB) [25]. Nonetheless, the mechanisms associated with this process have remained elusive until recently.…”
Section: Extent Of Phospholipid Saturation and Cell Signalingmentioning
confidence: 99%